Critical Analysis on Student’s Entrepreneurship Development Influencing Factors - Kumar, Dilip; Sengar, RS; Shrivastava, P; Singh, PR (International Journal of Computer Sciences and Engineering, 2025)
The present study was conducted under the jurisdiction of Indira Gandhi Krishi Vishwavidyalaya, Raipur (C.G.). The total 362 Final year (4th year) Under Graduate students have been selected randomly as respondents from 15 agricultural colleges. The primary data collected through pre tested structured interview schedule. Out of the total 362 respondents, majority of them (64.64%) were male and 35.36 per cent were female, majority (60.77%) of them were from the rural area, most (27.62%) of them had small size of land holding (up to 1 ha) and most (49.72%) of them had annual family income upto ₹ 1,00,000/-. Variables namely gender, family annual income, caste and size of land holding had significant and positive relationship with entrepreneurial behavior of respondents